2013
DOI: 10.1111/1756-185x.12087
|View full text |Cite
|
Sign up to set email alerts
|

Scientometric analysis and mapping of scientific articles on Behcet's disease

Abstract: This is the first scientometric analysis of BD, showing the scientometric characteristics of ISI publications on BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…found that Turkey, Japan and the USA occupied the first three places in NP (Fig. ) . Therefore, we measured a productivity score for each county and this score changed the ranking of the countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…found that Turkey, Japan and the USA occupied the first three places in NP (Fig. ) . Therefore, we measured a productivity score for each county and this score changed the ranking of the countries.…”
Section: Discussionmentioning
confidence: 99%
“…1). 2 Therefore, we measured a productivity score for each county and this score changed the ranking of the countries. Thus, Mediterranean countries took the lead in the ranking due to the productivity scores (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BD has distinctive geographical distribution, and it is found primarily in populations along the ancient Silk Route from the Mediterranean region transiting through Central Asia to East Asia [2]. The reported prevalence of BD varies between Western (0.12-7.5 per 100,000) [3] and Eastern countries (6.3-14 per 100,000) [4]. Turkey has the highest incidence of BD in general population (80-420 per 100,000) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%